Environmental filtering and deforestation shape frog assemblages in Amazonia: An empirical approach assessing species abundances and functional traits. (5th December 2021) - Torralvo, Kelly; de Fraga, Rafael; Lima, Albertina P.; Dayrell, Jussara; Magnusson, William E.
Abstract: Biological assemblages are often predictable from knowledge of natural environmental heterogeneity and change in response to anthropogenic disturbances, such as deforestation, so understanding ecological mechanisms and processes mediating assemblages is essential to direct conservation actions. We sampled frogs along an edaphic and vegetation‐structure gradient in the Brazilian Amazon to test the hypothesis that assemblages change in species composition and functional trait characteristics across landscapes due to environmental filtering. Our study area covered a gradient of forest fragmentation, and we hypothesized that assemblages would change in response to both natural gradients and deforestation. We found that frog assemblages are locally structured by species turnover along gradients in distance to water bodies, vegetation structure, soil sand and silt content, and proportion of the area deforested. Additionally, we found that small‐bodied species and those with direct breeding (no larval stage) were no longer present in deforested areas. We conclude that frog assemblages are not randomly distributed across forests, but trait filtering has resulted in different species subsets from the regional pool, which change among sites with different environmental conditions and disturbance levels. Our findings highlight the importance of creating reserves to effectively protect forests and maintain connectivity among forest fragments resulting from deforestation. Abstract in Portuguese is available with online material. Abstract : We sampled frogs along an edaphic and vegetation‐structure gradient in the Brazilian Amazon to test the hypothesis that assemblages change in species composition and functional trait characteristics across landscapes due to environmental filtering. We found that frog assemblages are locally structured by species turnover along gradients in distance to water bodies, vegetation structure, soil sand and silt content, and proportion of the area deforested and that small‐bodied species and those with direct breeding (no larval stage) were no longer present in these areas. Our findings highlight the importance of creating reserves to effectively protect forests and maintain connectivity among forest fragments resulting from deforestation. RESUMO: As assembleias biológicas são frequentemente previsíveis a partir do conhecimento da heterogeneidade ambiental natural e da mudança em resposta a distúrbios antrópicos, como o desmatamento, portanto, compreender os mecanismos e processos ecológicos que mediam as assembleias é essencial para direcionar as ações de conservação. Amostramos sapos ao longo de áreas que formam um gradiente edáfico e na vegetação na Amazônia brasileira para testar a hipótese de que as assembleias mudam na composição de espécies e características funcionais devido à filtragem ambiental. Nossa área de estudo cobriu um gradiente de fragmentação florestal e formulamos a hipótese de que as assembleias mudariam em resposta aos gradientes naturais e ao desmatamento. Descobrimos que as assembleias de anuros são localmente estruturadas pela troca de espécies ao longo de gradientes de distância aos corpos d'água, estrutura da vegetação, conteúdo de areia e silte do solo, e proporção da área desmatada. Além disso, descobrimos que as espécies de corpo pequeno e aquelas com reprodução direta (sem estágio larval) não estavam mais presentes nas áreas desmatadas. Concluímos que as assembleias de anuros não são distribuídas aleatoriamente pelas florestas, mas a filtragem de características resultou em diferentes subconjuntos de espécies do pool regional, que mudam entre locais com diferentes condições ambientais e níveis de desmatamento. Nossas descobertas destacam a importância de criar reservas para proteger as florestas de forma eficiente e para manter a conectividade entre os fragmentos florestais resultantes do desmatamento.